Sustainable tourism development: Mountainous area of Lam Dong province - Do , Thị Hiên; Pham , Trịnh Hồng Phi (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
Promoting the development of sustainable tourism models in Lam Dong province is an important factor in the development of mountainous tourism. In this article, we have considered how to develop tourism based on the available resources of the mountainous region of Lam Dong province: diversity in climate, flora and fauna, soil, and natural landscape. This is the province’s distinct strength, representing the common interests that must be maintained and developed to exploit sustainable tourism. In addition, we have analyzed the relationship between sustainable tourism models and natural resource management, applying new digital technologies to bring tourism benefits. The study emphasizes that the connection between public and private management models can ensure the growth and development of mountainous tourism areas in Lam Dong province.